Endoscopy-assisted pars plana lensectomy for brunescent cataracts in eyes with microcornea with microphthalmos. (2nd January 2022) - Parameswarappa, Deepika C; Dave, Vivek Pravin; Tyagi, Mudit; Pappuru, Rajeev R
ABSTRACT: Purpose: Conventional cataract surgeries can be a challenge in eyes with microcorneas due to difficult manipulation in a crowded anterior chamber (AC) and can lead to a high occurrence of corneal edema and an increased rate of complications. Similarly, in cases of dense brunescent cataracts even a lensectomy through posterior approach may prove to be difficult because of inadequate visualization. An endoscopyassisted pars plana lensectomy can help in obviating these difficulties. This study aims to describe the surgical technique of endoscopy-assisted pars plana lensectomy in eyes with brunescent cataract, microcornea, and microphthalmos. Methods: Retrospective review of two cases where endoscopy-assisted pars plana vitrectomy and lensectomy was performed for patients with dense cataract and microcornea and microphthalmos. Result: Complete clearance of the cataract was achieved without having to resort to a sclerocorneal incision. Postoperatively the cornea was clear and there was no postoperative corneal edema. Conclusion: Endoscopy-assisted pars plana lensectomy can help in overcoming the challenges of conventional anterior and posterior approaches of cataract extraction in cases of microcornea with reduced intraoperative and postoperative complications.